Linear Matrix Inequality Based Controller used in Multivariable Systems - Nagarajapandian, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
In industries most of the process are non-linear in nature. Inorder to overcome this problem most of the industries modify the loop and make it as Single Input and Single Output (SISO) controllers to regulate such processes inorder to obtain the fast and quicker settling. But some processes with numerous variables causes lot of complexities, there is a high demand for designing a multivariable system in process industries. One such multivariable process is the quadruple tank systems which are a multivariable process. It is non-linear and dynamic, but the challenging task is to maintain the level of tanks due to the interaction between the process variable. This paper is based on using LMI (Linear Matrix inequalities) and Model Reference Adaptive control (MRAC) tuned PI controller for controlling the level of the four tanks. All the experimental results for various tanks are obtained using MATLAB software. Â© 2019 IEEE.